A134 HIGH ADHERENCE TO SURVEILLANCE GUIDELINES IN IBD RESULTS IN LOW CRC AND DYSPLASIA RATES, WHILE RATES OF DYSPLASIA AND CANCER ARE LOW BEFORE THE SUGGESTED START OF SURVEILLANCE. RESULTS FROM A TERTIARY IBD CENTER. (15th March 2019) - Singh, K; Al Khoury, A; Kurti, Z; Gonczi, L; Reinglas, J; Verdon, C; Kohen, R; Bessissow, T; Afif, W; Wild, G; Seidman, E G; Bitton, A; et al.
Abstract: Background: Patients with Crohn's disease(CD) and ulcerative colitis(UC) are at increased risk for colorectal dysplasia(CRD) and cancer(CRC). Adherence to CRC surveillance guidelines is reported to be low internationally. Aims: Our aim was to evaluate surveillance practices at the tertiary IBD Center of the McGill University Health Center(MUHC) and to determine CRD/CRC incidence rates. Methods: A representative IBD cohort with at least 8 years of disease duration (or with PSC) who visited the MUHC between July 1-December 31, 2016 were included. Adherence to surveillance guidelines was compared to modified 2010 BSG guidelines. Incidence of CRC, high-grade dysplasia(HGD), low-grade dysplasia (LGD) and colorectal adenomas (CRA) were calculated based on pathology reports. Results: 1356 CD and UC patients (disease duration: 12 (IQR:6–22) and 10 (IQR: 5–19) years) were identified. The surveillance cohort consisted of 689 patients (296 UC and 384 CD). 91.5% of patients had at least one surveillance colonoscopy. Adherence to surveillance guidelines was 75.6/82.1% in UC/colonic CD. Adequate number of biopsies were taken in 53.7/54.2% of UC/colonic CD patients. Incidence of CRC/HGD in UC and CD with colonic involvement was 19.5/58.5 and 25.1/37.6 per 100, 000patient-years. Incidence of dysplasia before 8 years of disease duration was low in both UC/CD (19.5 and 12.5/100, 000 patient-years) with no patients developing CRC. The CRA rate was 30/38% in UC/colonic CD. Conclusions: High adherence with surveillance guidelines and overall low CRC and dysplasia, but not CRA rates were found in the screened population, suggesting that meeting updated, stratified, surveillance recommendations may result in low advanced neoplasia rates. CRC and dysplasia rates incidentally detected before the suggested start of the surveillance were low. Funding Agencies: McGill Departement of Medicine CAS Research Support